Dilemmas over individual and state responsibility for violations of international humanitarian law - Mengjo Keneth Lukong (Međunarodni Problemi, 2004)
This paper attempts an explanation to some of the complex legal issues surrounding the whole concept of responsibility for violations of international humanitarian law. The arguments here are based on reflections on the draft articles on the responsibility of states for the violations of international humanitarian law adopted by the international law commission as well as opinions of experts on the subject, treaties, conventions international jurisprudence, and internationally recognized principles and customs that govern conduct in armed conflicts so as to limit human suffering particularly of non combatants.